THE TRANSCENDENCE OF “EGO”: ETHICAL, METAPHYSICAL AND THEOLOGICAL APPROACHES - Морозов, А. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of “ego” as the metaphysical and meta-temporal centre of personality is observed.